2018
DOI: 10.1183/13993003.02431-2017
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors and prognostic significance of thromboembolic disease in patients with advanced ALK-rearranged non-small cell lung cancer

Abstract: Incidence, predictors and prognostic significance of thromboembolic disease in patients with advanced ALKrearranged non-small cell lung cancer To the Editor: Thromboembolic disease is fairly common in patients with lung cancer [1-3]. This incidence seems to be higher in patients with lung adenocarcinomas [4], with approximately 15% of those with advanced stage disease developing venous thromboembolisms (VTE) during the whole course of their disease [5-7]. Pulmonary adenocarcinomas are a heterogeneous group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
(11 reference statements)
1
20
0
Order By: Relevance
“…A 2018 study, including 241 patients with ALK rearrangement collected from 30 centers in Spain and Portugal but without a control or comparator group (and therefore no risk analysis), reported a VTE rate of 30%. 23 One previous study did perform survival analysis as we did but included just 33 patients with the ALK rearrangement. 22 This study reported a VTE rate of 27% in patients with ALK rearrangement with an SHR for VTE of 2.47 (95% CI: 1.04-5.90) relative to other patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2018 study, including 241 patients with ALK rearrangement collected from 30 centers in Spain and Portugal but without a control or comparator group (and therefore no risk analysis), reported a VTE rate of 30%. 23 One previous study did perform survival analysis as we did but included just 33 patients with the ALK rearrangement. 22 This study reported a VTE rate of 27% in patients with ALK rearrangement with an SHR for VTE of 2.47 (95% CI: 1.04-5.90) relative to other patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports of severe hypercoagulable states in ALK-rearranged NSCLC have been published, [14][15][16] describing severe decompensated disseminated intravascular coagulation with thrombosis or recurrent venous and arterial events despite escalating anticoagulant and antiplatelet regimens. Previous observational studies have also specifically evaluated the risk of VTE in ALK-rearranged NSCLC [17][18][19][20][21][22][23] with highly variable and conflicting results, although each of these studies had several important limitations, including one or more of small sample sizes, lack of time-to-event (survival) analysis, lack of a control group, and failure to control for critical covariates, confounders, and the competing risk of death. In addition, none of these studies evaluated the separate and distinct risk of arterial thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in order to demonstrate a direct correlation between ICIs and TE events, a control arm of patients with similar characteristics not receiving immunotherapy would have been optimal. However, this comparison is hard to perform, since NSCLC patients treated with chemotherapy are at even higher risk of TE events, as are patients with driver mutations receiving targeted therapies [54][55][56]. Moreover, if tested, lower rates of PD-L1 positivity would be found in these populations, as this might represent the reason to omit ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of thrombosis in these patients varies widely, so it is important to identify patients at higher risk of developing VTE whom prophylaxis may be beneficial. Recently, VTE incidence over 30% have been described in pancreatic cancer [17,18] and specific molecular subtypes of non-small cell lung cancer (NSCLC) with ROS-1 [19] and ALK rearrangement [20,21]. Cancer patients are usually unaware of VTE risk [22].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%